Where did it go? - Guibert, Grace (Chicago World books inc, 2018)
Describes methods of camouflage and mimicry used by leaf-tailed geckos, snowy owls, orchid mantises, and other animals. Includes large photographs and relevant information about each animal presented.
Kids Ages 5-11